RIS-based indoor wireless communication signal enhancement system - Kui TANG; Qi HU; Junming ZHAO; Ke CHEN; Yijun FENG (Tongxin xuebao)
By utilizing the tunable performances of the reconfigurable intelligent surface (RIS) to manipulate the reflected electromagnetic waves, an indoor wireless communication signal enhancement system was constructed, which could improve the signal quality of the receiving terminal in where the initial wireless signals were weak.First, a RIS unit cell with dynamically tunable phase characteristics was designed, and the dynamic change of the 2 bit reflection phases was realized by switching the working states of the two active diodes.Then, experiments were conducted to verify that the proposed RIS could dynamically reshape the beam direction.Finally, a host computer and field programmable gate array (FPGA) were used to realize the intelligent control of the coding sequences applied onto the proposed RIS.By changing the spatial phase distribution on the RIS aperture, the output beam could be controlled in real-time.By traversing the pre-loaded coding sequences, the enhancement of received signal in indoor wireless environments had been experimentally demonstrated.Both simulation and experiment results verify that the proposed RIS system can effectively and dynamically improve the quality of the indoor wireless signals.The received signal is increased by an average of 8.9 dB, with a maximum of 22 dB.The proposed work may provide basic hardware technical support for the optimization of 5G and the next-generation communication networks.